Academic Writing Difficulties of Bangladeshi Students at a Higher Institution in Malaysia - Mizanur Rahman; Kamrul Hasan (Journal of Research and Multidisciplinary, 2019)
Students who come from non-English background and pursue study in English at tertiary level in Asia, particularly in Bangladesh face great difficulty in their academic writing classes. In order to improve learners’ academic writing, teaching of academic writing in classrooms plays a vital role in English language classrooms/higher education since in most of the language courses, academic writing skill is never taught at tertiary education in Bangladesh. Considering the backdrop into consideration, this study aimed to investigate the academic writing difficulties encountered by Bangladeshi students at University Utara Malaysia (UUM). To this end, under survey design, primary data were collected by conducting survey questionnaires; 38 Bangladeshi students were selected by using non-probability purposive sampling technique. Data of this study were analysed, employing SPSS (22 version) software package. From the significance test of the first hypothesis, the study found that the influencing factors had significant impact on academic writing difficulties of Bangladeshi students at UUM. And from the second hypothesis, the current study found that the potential problems had also significant impact on academic writing difficulties of Bangladeshi students at UUM. Finally, some recommendations have been proposed to overcome academic writing difficulties of Bangladeshi student at UUM